Radio frequency interface quality assessment in 4G/5G: Effects of IQ imbalance, phase noise, and nonlinearities on error vector magnitude - Ilya Pyatin; Juliy Boiko; Viacheslav Kovtun; Oksana Kovtun (PLoS ONE, 2025)
Modern 4G/5G technologies aim to enhance data speeds, improve communication quality, and enable innovative services such as IoT and augmented reality. However, their efficiency depends on minimizing distortions in the radio frequency (RF) interface, evaluated through Error Vector Magnitude (EVM). Increased EVM leads to packet losses and reduced throughput, making its reduction essential for stable and high-quality networks. This study investigates the impact of RF interface imperfections on EVM in 4G/5G systems. The analysis was conducted using Simulink models of digital communication transmitters and receivers, incorporating in-phase and quadrature (IQ) imbalance, phase noise, power amplifier (PA) nonlinearity, channel noise, and signal-coding scheme characteristics. The QM78207 chipset, integrating key RF components, was used as an example to reflect the complexity and quality requirements of modern RF interfaces. The results show that the maximum allowable EVM for 64-QAM is 8% (-22 dB). Variations in IQ amplitude imbalance (0–3 dB) increased EVM from -32 dB to -15 dB, while IQ phase imbalance (0°–15°) caused an increase from -32 dB to -17 dB, both for SNR = 50 dB. These findings are valuable for optimizing RF interface designs in 4G/5G systems, ensuring enhanced communication quality and supporting the growing demands for advanced services.